2015
DOI: 10.1071/py13102
|View full text |Cite
|
Sign up to set email alerts
|

Role of public transport in accessibility to emergency dental care in Melbourne, Australia

Abstract: The aim of this study was to develop a method for the analysis of the influence of public transport supply in a large city (Melbourne) on the access to emergency dental treatment. Geographic Information Systems (GIS) tools were used to associate the geographical distribution of patients (and their socioeconomic status) with accessibility (through public transport supply, i.e. bus, tram and/or train) to emergency dental care. The methodology used allowed analysis of the socioeconomic status of patient residenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Descriptive statistical analysesincluding practice-topopulation ratioswere conducted using Microsoft Excel (version 2016, Microsoft, Redmond, WA, USA). These methods were consistent with past papers resting upon descriptive statistics alone 16,17 .…”
Section: Statistical Analysessupporting
confidence: 88%
“…Descriptive statistical analysesincluding practice-topopulation ratioswere conducted using Microsoft Excel (version 2016, Microsoft, Redmond, WA, USA). These methods were consistent with past papers resting upon descriptive statistics alone 16,17 .…”
Section: Statistical Analysessupporting
confidence: 88%
“…8 Oral healthcare system, insurance status, competence of health professionals, working hours, public transport, disabled children, economic and social barriers are identified as important factors for access to emergency dental care. 8,[18][19][20] A much lower level was found in this study, and significant clues were obtained to understand why.…”
Section: Discussionmentioning
confidence: 46%
“…Alnaggar and Andersson reported that treatment of traumatic dental injuries within the first hour was accessed by only 53% and reached an adequate treatment at a rate of 56% out of working hours . Oral healthcare system, insurance status, competence of health professionals, working hours, public transport, disabled children, economic and social barriers are identified as important factors for access to emergency dental care . A much lower level was found in this study, and significant clues were obtained to understand why.…”
Section: Discussionmentioning
confidence: 52%
“…Accordingly, it is possible that at‐risk populations—with infrequent transport options—are dissuaded from seeking appointments for urgent care in São Paulo city . By contrast, advantaged populations—with lower dental disease prevalence—typically live within walking distance of primary dental care, and likely have access to private transportation if seeking treatments further away …”
Section: Discussionmentioning
confidence: 99%
“…One problem faced by studies of public transportation supply is defining a meaningful standard of service. In Melbourne, Australia, a neighbourhood is considered to be serviced by public transportation if it is located within 0.4 km of a bus or tram stop, or 0.8 km of a train station . No such definitions were available for São Paulo city.…”
Section: Methodsmentioning
confidence: 99%